ESTIMASI MAXIMUM LIKELIHOOD DAN RESTRICTED MAXIMUM LIKELIHOOD UNTUK MODEL LINEAR EFEK CAMPURAN - , ADIANTO PANGARIBUAN ([Yogyakarta] : Universitas Gadjah Mada, 2014)
Linier mixed effects model (LME) is one of parametric linier regression for clustered, longitudinal, or repeated measures data that quantifies the relationship between a continous dependent variabel and independent variable. LME may include both fixed effects parameters and random effects. Estimation parameter of LME can be achieved using maximum likelihood estimation and restricted maximum likelihood method with multivariate normal distribution from the marginal model. Random effects coefficient from the model can be predicted using conditional expectation. The best model selection using the likelihood ratio test alongside with Akaike Information Criterion (AIC) and Bayesian Information Criterion (BIC). The best method estimation selection using mean square error. LME is applied to real data, the examination of pregnant woman in Community Health Center in Yogyakarta.